Answer:i am confused what is the question i will help tho
Step-by-step explanation:
Answer:
<em>g(</em><em>x)</em><em> </em><em>=</em><em> </em><em>-4g(</em><em>x)</em><em> </em><em>=</em><em> </em><em>-x+</em><em>4</em>
<em>=</em><em> </em><em>g(</em><em>5</em><em>)</em><em> </em><em>=</em><em> </em><em>-</em><em>4</em><em>(</em><em>5</em><em>)</em><em> </em><em>=</em><em> </em><em>-</em><em>(</em><em>5</em><em>)</em><em>+</em><em>4</em>
<em>=</em><em> </em><em>g(</em><em>5</em><em>)</em><em> </em><em>=</em><em> </em><em>-</em><em>2</em><em>0</em><em> </em><em>=</em><em> </em><em>-</em><em>1</em>
So the equation for these types of equations is f(x) = a(x-h)+k with h being a horizontal translation, a being a stretch/compression and k being a vertical translation. So here if you want a stretch of 4 a would be four, g(x)=4(-3x-h)+k. Also, there is a horizontal translation so it would be positive 4 into the equation. Since there is no change in the y-axis there is no vertical translation resulting in g(x) = 4(-3x-4)